Reliability analysis of Rio Chico dela Pampanga River Basin as additional source of irrigation water for the Balog-Balog Irrigation System - Ballatan, Gilmar J.
The single high dam of the Balog-Balog Multipurpose Project (BBMP) is designed to use the surface runoff from the headwaters of Tarlac-O'Donnell River Basin to irrigate 34,410 hectares of riceland of the Balog-Balog Irrigation System (BIS), located across the central plains of three converging basins: Talavera, Rio Chico dela Pampanga and Tarlac-O'Donnell. However, additional irrigation water sources for the BIS is needed, as hectares for the wet and dry seasons, respectively (Tabios, 2015). This study aims to identify the possible additional water source to augment the BBMP supply and reduce transbasin supply allocation to other basins. Three schemes of development, for rice-rice cropping, were evaluated for Parua River in Tarlac: (1) reservoir, (2) diversion, and, (3) reservoir-diversion combination. The reliability, in terms of irrigated area, of the Parua River as an additional source for the BIS service area at different scenarios were fashioned by varying the dam height, total overall efficiency and the inactive zone capacity (sedimentation) of the proposed schemes of development. Result of the different scheme combinations shows that the Parua River is a potential additional source for the BIS service area. Estimates of the source's reliability is significantly affected by the total overall efficiency of the system and less significantly affected by the dam height and the inactive zone capacity. In general, the development of Parua River as additional source may significantly increase irrigation supply to the BIS, reducing transbasin supply allocation from Tarlac-O'Donnell River Basin to the BIS.